THESTRENGTHASSESSMENTOFTHESHOCKINTERACTIONOFWHEELANDRAILATTHEJUNCTIONOFTWORAILS - Manashkin, L. A.; Myamlyn, S. V.; Prykhodko, V. Y. (Science and Transport Progress, 2008)
In the article some variants of a wheel passing a joint from rail to rail are considered and the forces occurring in this process are estimated. The related mathematical description of the wheel-rail shock interaction is proposed.